Effect of a Feed Additive Based on Organic Acids and Tangerine Wort (Citrus reticulata) as Growth Promoter for Broiler Chickens - Mazzero, Leonardo; Andrade, J. M.M.; Moreira, H.; Valvano, I. M. [UNESP]; Menten, J. F.M. (FapUNIFESP (SciELO), 2023)
Feed additive alternatives to antibiotics, such as organic acids, and substances rich in polyphenols, such as tangerine wort, can promote improved intestinal health in broilers by modulating the microbial population and improving nutrient utilization. In this work, a product which combines organic acids (fumaric acid 0.5%, lactic acid 5.13%, citric acid 5.44% and ascorbic acid 1.2%) and tangerine wort (Citrus reticulata) 8.36% was studied. To determine the effect and the most appropriate level of inclusion of product in the diet of broilers, an experiment was carried out with 1400-day-old male chicks, in a conventional poultry house, evaluating the performance until 42 days of age. The birds were housed in RCB design with 5 treatments and 7 replicates of 40 birds each, and the diets with the additive inclusions were evaluated: A250 (250 mg/kg), A500 (500 mg/kg), A1000 (1000 mg/kg), a negative control (NC, not supplemented), and a positive control (PC, 10 mg/kg of enramycin). The diets were formulated based on corn and soybean meal, containing added phytase and without anticoccidial; the additives replaced an inert in the basal diet. Performance characteristics, microbiota count, morphometry and jejunum morphology were evaluated. Considering the overall experimental period, the inclusion of the alternative additive based on organic acids and tangerine wort at different levels (250, 500 and 1000 mg/kg) did not result in difference from the negative control diet or the positive control with the inclusion of the antibiotic enramycin for performance traits (p>0.05), as well as for the microbiota count, morphology, jejunal morphometry and viability. Considering the period of 29-35 days alone, treatment with 500 mg/ kg of alternative additive improved weight gain and feed intake of the chickens (p<0.05), but had no effect on feed conversion.
Keywords: Antibiotic free; Broiler; Flavonoids; Organic acids